High speed rail competition in Italy: A major railway reform with a "win-win game"? - Christian Desmaris (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
The European railway industry continues to undergo reform and liberalization due to European law incentives. Recent events in Italy give the country a special place in this process: a new competitor has commenced operations in the high-speed rail (HSR) market based on a private initiative. This paper aims to investigate this rail transport innovation looking for the driving forces and obstacles and to identify the main impacts for the Italian consumers. We also try to provide some interesting results helpful for other countries regarding passenger rail reforms. Based on the Italian case, it seems that open access competition in the HSR market is able to produce significant improvements in favour of passengers and also a "win-win" game between all railway actors.
Keywords: 330; Hochgeschwindigkeitsverkehr; Bahnpolitik; Ausschreibung; Wettbewerb; Italien